2022
DOI: 10.1002/ijfe.2620
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the impact of corporate governance and intellectual capital on financial performance: A longitudinal study of Deutsche Bank (1957–2019)

Abstract: This article empirically examines the nexuses between corporate governance, intangible resources, CEO traits, and financial performance. In contrast to prior research, this study examines these relationships in a longitudinal manner focusing on Deutsche Bank for the 1957-2019 period. To the best of our knowledge, this study is the first of its kind. Based on a novel hand collected dataset, our analysis suggests a significant positive relationship between intangible assets i.e., intellectual capital efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
3
19
0
2
Order By: Relevance
“…A similar level was considered by Kianto, Andreeva, and Pavlov (2013) as quite significant, considering how many other issues affect competitive performance. The results are coherent with other studies examining the IC impact on financial performance (e.g., Neves & Proença, 2021;Yaseen & Al-Amarneh, 2021;Nawaz & Ohlrogge, 2022;Rehman, Aslam & Iqbal, 2022) and competitive performance measured by market share (e.g., Rehman, Aslam & Iqbal, 2022) although they applied research methodology. H2: Competitive performance has a moderator effect on the relationship between IC and financial performance.…”
Section: The Assessment Of the Structural Modelsupporting
confidence: 88%
See 2 more Smart Citations
“…A similar level was considered by Kianto, Andreeva, and Pavlov (2013) as quite significant, considering how many other issues affect competitive performance. The results are coherent with other studies examining the IC impact on financial performance (e.g., Neves & Proença, 2021;Yaseen & Al-Amarneh, 2021;Nawaz & Ohlrogge, 2022;Rehman, Aslam & Iqbal, 2022) and competitive performance measured by market share (e.g., Rehman, Aslam & Iqbal, 2022) although they applied research methodology. H2: Competitive performance has a moderator effect on the relationship between IC and financial performance.…”
Section: The Assessment Of the Structural Modelsupporting
confidence: 88%
“…Some authors add a fourth component connected with the influence of technology on the financial service industry (Shih, 2008). On the contrary, others use a synthetic measure to examine the IC efficiency, such as as HCE, SCE and RCE (Poh, Kilicman & Ibrahim, 2018;Rehman, Aslam & Iqbal, 2022) or employ VAIC or other similar methods such as VAICTM to analyze the performance of banks, focusing on IC and its influence on different aspects of banks' market position (Cabrita & Vaz, 2006, Mavridis, 2005Alhassan & Asare, 2016;Goh, 2005;El-Bannany, 2008;Al-Musali & Ismail, 2014;Singh, Sidhu, Joshi & Kansal, 2016;Mohammed & Irbo, 2018;Umanto & Atmoko, 2018;Xu, Haris & Yao, 2019;Neves & Proença, 2021;Yaseen & Al-Amarneh, 2021) or base their research on case studies (Murthy & Mouritsen, 2011;Hosseini & Owlia, 2016;Nawaz & Ohlrogge, 2022). Measuring IC using a survey is still unique (Cabrita & Bontis, 2008;Curado, 2008;Mention & Bontis, 2013).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found that the company's failure to manage the company was caused by the structure and mechanism of GCG that did not work well, causing many irregularities. Many studies about GCG have been studied, studies [7], [19], [20], [22] explain that companies that are effective in implementing GCG will reduce the risk of companies experiencing financial distress. GCG variables often used are institutional ownership, size of the board and audit committee.…”
Section: B Good Corporate Governance Mechanismmentioning
confidence: 99%
“…According to this hypothesis, external market pressures are forced to discipline inefficient boards, thereby improving the operational effectiveness of the acquired bank 8 . An increasing number of studies investigate the effects of board size and composition on bank performance (Adnan et al, 2011; Agoraki et al, 2010; Nawaz & Ohlrogge, 2022; Pi & Timme, 1993; Polyzos et al, 2018). Compared with stock banks, there is little literature on this subject for financial cooperatives.…”
Section: Brief Survey Of the Literaturementioning
confidence: 99%